Balancing Books and Brooms: Gender Disparities in Household Chores and Their Impact on Academic Stress - Dr. Leenah Ãskaree; Javeriya; Zumra Zafar (Indus Journal of Social Sciences, 2025)
The unequal distribution of household chores based on gender norms has profound implications for students’ academic stress. Traditional societal expectations often place a greater domestic burden on female students, leaving them with limited time and energy to focus on academic pursuits. This study examines the relationship between gender-based disparities in household responsibilities and the resulting levels of academic stress among university students. Results reveal that female participants engage in a disproportionate share of household tasks compared to male counterparts, contributing to heightened academic stress (Hochschild & Machung, 2012). Furthermore, cultural norms and traditional gender roles exacerbate this imbalance, intensifying emotional and physical strain (Eagly, 1987). Incorporating both cross-cultural perspectives and Islamic teachings, which emphasize equity and fairness in domestic responsibilities (The Quran, 16:97), the study offers nuanced insights into the intersection of societal expectations, gender, and education. The findings underscore the necessity for gender-equitable practices in households and suggest institutional interventions to support students burdened by academic stress.